Thermodynamic and electrical transport investigation of URu2Si2−xPx. (14th November 2016) - Gallagher, A; Chen, K-W; Cary, S K; Kametani, F; Graf, D; Albrecht-Schmitt, T E; Shekhter, A; Baumbach, R E
Abstract: Magnetic susceptibility, electrical resistivity, and heat capacity results are reported for the chemical substitution series URu2 Si2− x P x for 0 < x ≲ 0.5 . This study expands in detail on work recently reported in Gallagher et al (2016 Nat. Commun . 10712), which focused on the small x region of this substitution series. Measurements presented here reveal persistent hybridization between the f - and conduction electrons and strong variation of the low temperature behavior with increasing x . Hidden order and superconductivity are rapidly destroyed for x ≲ 0.03 and are replaced for 0.03 ≲ x ≲ 0.26 by a region with Kondo coherence but no ordered state. Antiferromagnetism abruptly appears for x ≳ 0.27 . This phase diagram differs significantly from those produced by most other tuning strategies in URu2 Si2, including applied pressure, high magnetic fields, and isoelectronic chemical substitution (i.e. Ru  →  Fe and Os), where hidden order and magnetism share a common phase boundary. Besides revealing an intriguing evolution of the low temperature states, this series provides a setting in which to investigate the influence of electronic tuning, where probes that are sensitive to the Fermi surface and the symmetry of the ordered states will be useful to unravel the anomalous behavior of URu2 Si2 .